How does Europe's best table tennis player, Dimitrij Ovtcharov, hold his ground throughout the matches against the four best Chinese players? - Straub, G. (Proceedings Book of The 15th ITTF Sports Science Congress Düsseldorf, 27th - 28th May 2017, 2017)
Prior to the Olympic Games of Rio de Janeiro, Germany´s ranked number five player in the world (as of July 2016), Dimitrij Ovtcharov, underlined his claim to challenge the Chinese competitors. In considering this proposition, an analysis using the three-phase method of performance diagnosis was done in regard to 18 matches against the four players ranked ahead of the German in the ITTF world ranking list. Taken on the whole, the results show that the playing strength of Fan Zhendong, Ma Long, Xu Xin and Zhang Jike is very much superior to the performance of Dimtrij Ovtcharov. But this does not mean that the German did not win any matches or that he was not able to keep up with his opponents in some situations, or stages of the rallies. For Dimitrij Ovtcharov, the chance to win is not tremendously but comparatively high when encountering Zhang Jike. A decent serve-and-return play seems to be required, based either on an excellent serving or a superb receiving behavior. In addition, for both players, the behavior in stalemate situations (after ball contact number four) seems to have a marked influence on their total match outcomes. In his matches against Zhang, Fan, and Xu, the German usually shows an acceptable or even good serving behavior. On the basis of the quality work already done in this respect, the receiving behavior of Dimitrij Ovtcharov probably has the strongest impact on his competition performance against the world´s very best players.